Ribosomal DNA as DAMPs Signal for MCF7 Cancer Cells - Malinovskaya, Elena M.; Ershova, Elizaveta S.; Okorokova, Natalya A.; Veiko, Vladimir P.; Konkova, Marina S.; Kozhina, Ekaterina A.; Savinova, Ekaterina A.; Porokhovnik, Lev N.; Kutsev, Serguey I.; Veiko, Nataly N.; Kostyuk, Svetlana V. (Frontiers in Oncology, 2019)
Introduction: The cell free ribosomal DNA (cf-rDNA) is accrued in the total pool of cell free DNA (cfDNA) in some non-cancer diseases and demonstrates DAMPs characteristics. The major research questions: (1) How does cell free rDNA content change in breast cancer; (2) What type of response in the MCF7 breast cancer cells is caused by cf-rDNA; and (3) What type of DNA sensors (TLR9 or AIM2) is stimulated in MCF7 in response to the action of cf-rDNA? Materials and Methods: CfDNA and gDNA were isolated from the blood plasma and the cells derived from 38 breast cancer patients and 20 healthy female controls. The rDNA content in DNA was determined using nonradioactive quantitative hybridization. In order to explore the rDNA influence on MCF7 breast cancer cells, the model constructs (GC-DNAs) were applied: pBR322-rDNA plasmid (rDNA inset 5836 bp long) and pBR322 vector. ROS generation, DNA damage, cell cycle, expression of TLR9, AIM2, NF-kB, STAT3 and RNA for 44 genes affecting the cancer cell viability were evaluated. The methods used: RT-qPCR, fluorescent microscopy, immunoassay, flow cytometry, and siRNA technology. Results: The ratio R= cf-rDNA/g-rDNA for the cases was higher than for the controls (median 3.4 vs 0.8, p<10-8). In MCF7, GC-DNAs induce a ROS burst, DNA damage response, and augmentation of NF-kB and STAT3 activity. The number of the apoptotic cells decreases, while the number of cells with an instable genome (G2/M– arrest, micronuclei) increase. Expression of anti-apoptotic genes (BCL2, BCL2A1, BCL2L1, BIRC3, MDM2) is elevated, while expression of pro-apoptotic genes (BAX, BID, BAD, PMAIP1, BBC3) is lowered. The cells response for pBR322-rDNA is much more intense and develops much faster, than response for pBR322, and is realized through activation of TLR9- MyD88 - NF-kB- signaling. This difference in response speed is owing to the heightened oxidability of pBR322-rDNA and better ability to penetrate the cell. Induction of TLR9 expression in MCF7 is followed by blocking AIM2 expression.